Content and structure of the self-educational competence of students in professional and technical education instittions - Sergey Osipenko (ScienceRise: Pedagogical Education, 2018)
Various approaches to understanding the essence of self-education make it possible to determine that self-education is based on the knowledge, skills, abilities and methods of learning activities acquired in the process of learning, manifested as an independent cognitive activity carried out by those who study.